Teaching Bahasa Indonesia for Polish Speakers Based on Moderate Muslim Culture - Jauharoti Alfin (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
The purpose of this paper is to explain the result of moderate Muslim culture immersion model development into the Bahasa Indonesia untuk Penutur Asing (Bahasa Indonesia for Non-Native Speakers [BIPA]) program in the faculty of New Philology, Adam Mickiewicz University in Poznan, Poland. The focus of the development is the research and development (R&D) stage, which comprises: preliminary study, development, and testing. This study uses the before-after comparative analysis method on an experimental group with a control group. It is concluded that the model is succeeded in significantly improving the understanding of the BIPA program students on moderate Muslim culture.